Performance Comparison of two Novel Combinative Particle‐Size‐Reduction Technologies. Issue 5 (21st February 2013) - Salazar, Jaime; Müller, Rainer H.; Möschwitzer, Jan P.
Abstract The nanosizing of poorly soluble drugs as a formulation strategy can eventually enhance their dissolution rate and bioavailability. Standard comminution techniques such as high‐pressure homogenization (HPH) or wet bead milling have limitations in reaching the desired mean particle size. Combinative methods have been developed to overcome these limitations. Combinations of a bottom‐up step (freeze‐drying or spray drying) with HPH (the so‐called H 96 and H 42 technologies, respectively) are examples of combinative particle‐size‐reduction technologies. The precipitation step modifies the drug structure to obtain a brittle starting material for the following homogenization process. Previous experiments using the H 96 technology have shown a relation between the bottom‐up conditions and the final particle size after the top‐down step. Employing the H 42 process, the poorly soluble drug glibenclamide was dissolved in ethanol, containing different amounts of surfactant. The drug solution was then spray dried. Subsequently, the drug powders were homogenized using the HPH technique. The nanosuspensions produced with the spray‐dried powders (high drug concentrations, standard surfactant concentration) had a smaller particle size and a narrower size distribution compared with the unmodified drug. The best sample had a 236 nm mean particle size (observed using photon correlation spectroscopy) and laser diffractometry values of 0.131 µm (D50) and 0.285 µm (D90) after 20 cycles of homogenization. The results were compared with the reduction effectiveness of a previous study employing the H 96 combinative process. Both combinative technologies can be successfully applied for the production of very small drug nanocrystals. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:1636–1649, 2013